Cardio and neuro protection by renin angiotensin aldosterone system-focus inhibition angiotensin converting enzyme: A systematic review - Capritasari Rafiastiana; Akrom; Setianto Arif Budi (BIO Web of Conferences)
One of the incidences of cardiovascular disease is stroke, which is a disease that occurs due to impaired brain function caused by damage to cerebral blood circulation. The presence of risk factors for hyperglycemia or hypertension can result in endothelial nitric oxide (eNOS) dysfunction, thereby causing oxidative stress and vasoconstriction of blood vessels. The renin angiotensin system is involved in the physiopathology of stroke and has an important impact on hypertension. This article targets the role of the renin angiotensin system specifically the inhibition of the angiotensin converting system in cardioprotection and neuroprotection. The mechanism of action of the renin-angiotensin-aldosterone system (RAAS) is observed through effects on AT1, AT2 and Mass receptors. The future relationship of cardiovascular disease and the renin-angiotensin system is full of possibilities, as new agonist molecules emerge as potential candidates to limit the impairments caused by cardiovascular disease.